1999
DOI: 10.1002/(sici)1097-4628(19991205)74:10<2470::aid-app16>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Hygrothermal aging and fracture behavior of styrene-acrylonitrile/acrylate based core-shell rubber toughened poly(butylene terephthalate)

Abstract: A study of hygrothermal aging in terms of the kinetics of moisture absorption by poly(butylene terephthalate) (PBT) and styrene-acrylonitrile/acrylate based core-shell rubber (CSR) toughened PBT (PBT-CSR) was undertaken. The diffusion of water into the PBT compounds with various CSR contents was investigated by immersion of specimens in water at temperatures between 30 and 90°C. It was observed that the equilibrium moisture content and the diffusion coefficient of the PBT both increased with increasing CSR con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…In the presence of organoclay, the segmental mobility of the polymer molecules and the plastic deformation process in the form of crazing and shear yielding are very much restricted at high deformation rates. The reduction of toughness of the materials with increasing testing speed was also reported for core‐shell rubber toughened PBT blends [23] and PETG/POM/TPU blends [24]. The increase in K IC value observed in the PA6/PP/4C‐MMT with increasing the testing speed may be attributed to the plasticizing effect caused by high content of organic modifier (octadecylamine) in the commercial organo‐MMT, i.e., 34%.…”
Section: Resultssupporting
confidence: 53%
“…In the presence of organoclay, the segmental mobility of the polymer molecules and the plastic deformation process in the form of crazing and shear yielding are very much restricted at high deformation rates. The reduction of toughness of the materials with increasing testing speed was also reported for core‐shell rubber toughened PBT blends [23] and PETG/POM/TPU blends [24]. The increase in K IC value observed in the PA6/PP/4C‐MMT with increasing the testing speed may be attributed to the plasticizing effect caused by high content of organic modifier (octadecylamine) in the commercial organo‐MMT, i.e., 34%.…”
Section: Resultssupporting
confidence: 53%
“…Poly(butylene terephthalate) (PBT) is an important engineering thermoplastic because of its good combination of properties,1, 2 such as rigidity, solvent resistance, and high rates of crystallization. The notched impact strength of PBT is very low, but it can be improved by the incorporation of elastomers 3–8. Until recently, the impact strength improvements with unmodified elastomers were moderate, but in the last few years, increases in the impact strength between 10‐ and 20‐fold have been achieved with the addition of functionalized elastomers to produce the so‐called supertough PBTs.…”
Section: Introductionmentioning
confidence: 99%
“…With an increase of single screw shear, fiber pull out can be seen in the fracture. 3 Furthermore, debonding between GF and PBT matrix became a common phenomenon and were clearly visible in the PBT matrix in Figure 3(e) to (h). It was found that the fracture of RPBT-3316-T30 show a brittleness matrix with GFs embedded into the PBT matrix.…”
Section: Morphology Of Samplesmentioning
confidence: 95%
“…Mohd Ishak et al. 1,3,4 reported that the glass fiber (GF) also provides a function of preventing the PBT matrix from being hydrolyzed. The complex orientation of short GF obstructed the diffusion of absorbed water molecules into the matrix and hence reduced the extent of the hydrolysis of PBT matrix.…”
Section: Introductionmentioning
confidence: 99%